A Survey on Reactive Programming - Bainomugisha, Engineer; Lombide Carreton, Andoni; Cutsem, Tom Van; Mostinckx, Stijn; Meuter, Wolfgang De (ACM Computing Surveys (CSUR), 2013)
Reactive programming has recently gained popularity as a paradigm that is well-suited for developing event-driven and interactive applications. It facilitates the development of such applications by providing abstractions to express time-varying values and automatically managing dependencies between such values. A number of approaches have been recently proposed embedded in various languages such as Haskell, Scheme, JavaScript, Java, .NET, etc. This survey describes and provides a taxonomy of existing reactive programming approaches along six axes: representation of time-varying values, evaluation model, lifting operations, multidirectionality, glitch avoidance, and support for distribution. From this taxonomy, we observe that there are still open challenges in the field of reactive programming. For instance, multidirectionality is supported only by a small number of languages, which do not automatically track dependencies between time-varying values. Similarly, glitch avoidance, which is subtle in reactive programs, cannot be ensured in distributed reactive programs using the current techniques.
Keywords: Reactive programming; Interactive applications; Event-driven applications; Dataflow programming; Functional reactive programming; Reactive systems